Peran Perawat dalam Mengatasi Diabetes Distress - Hasanah, Laila; Yulia, Yulia; Edison, Chiyar (Journal of Telenursing (JOTING), 2023)
This research aims to guide nurses in therapeutic communication with patients with diabetes distress. The method used in this writing is a literature review through several databases, namely Pubmed, ClinicalKey, Proquest, and Science Direct. The research results show that diabetes distress is a common thing experienced by patients with diabetes mellitus. In conclusion, treating diabetes distress is part of comprehensive diabetes management. Keywords: Diabetes Distress, Nurse's Role